Molecular characterization and transcriptional regulation analysis of the Torreya grandis squalene synthase gene involved in sitosterol biosynthesis and drought response - Feicui Zhang; Congcong Kong; Zhenmin Ma; Wenchao Chen; Yue Li; Heqiang Lou; Jiasheng Wu (Frontiers in Plant Science, 2023)
The kernel of Torreya grandis cv. ‘Merrillii’ (Cephalotaxaceae) is a rare nut with a variety of bioactive compounds and a high economic value. β-sitosterol is not only the most abundant plant sterol but also has various biological effects, such as antimicrobial, anticancer, anti-inflammatory, lipid-lowering, antioxidant, and antidiabetic activities. In this study, a squalene synthase gene from T. grandis, TgSQS, was identified and functionally characterized. TgSQS encodes a deduced protein of 410 amino acids. Prokaryotic expression of the TgSQS protein could catalyze farnesyl diphosphate to produce squalene. Transgenic Arabidopsis plants overexpressing TgSQS showed a significant increase in the content of both squalene and β-sitosterol; moreover, their drought tolerance was also stronger than that of the wild type. Transcriptome data from T. grandis seedlings showed that the expression levels of sterol biosynthesis pathway-related genes, such as HMGS, HMGR, MK, DXS, IPPI, FPPS, SQS, and DWF1, increased significantly after drought treatment. We also demonstrated that TgWRKY3 directly bound to the TgSQS promoter region and regulated its expression through a yeast one-hybrid experiment and a dual luciferase experiment. Together, these findings demonstrate that TgSQS has a positive role in β-sitosterol biosynthesis and in protecting against drought stress, emphasizing its importance as a metabolic engineering tool for the simultaneous improvement of β-sitosterol biosynthesis and drought tolerance.